Effects of One-Month Baby Massage by Mothers on Autonomic Nervous System Function and Growth Development of 4- and 5-Month-Old Infants - Yayoi Tanaka; Hiroko Watanabe (Women, Midwives and Midwifery, 2023)
Background: Massage has been practiced since around 3 months of age for the purpose of interacting with children, but there are few reports on its ongoing effectiveness, no unified views, and few reports on growth and development. Purpose: The purpose of this study was to examine the effects of massage given by mothers to their 3-month-old infants based on autonomic activity and growth development of 4- and 5-month-old infants one month later. Methods: The subjects were healthy 3-month-old infants and their mothers who were born as full-term, singleton babies. The study design was an inequivalent control group design: 25 mother-child pairs were massaged for one month and 12 mother-child pairs were not massaged. Data were collected twice, once on the first day at 3 months of age and one month later. As indicators of autonomic nervous system activity, axillary temperature before and after massage, heart rate and heart rate variability during massage were measured. As an indicator of growth, body weight was measured after the massage. As an indicator of development, mothers were asked to respond to a questionnaire (KIDS). The axillary temperature, rate of change in heart rate and heart rate variability, and KIDS scores were compared on the first day and one month later. Results: Axillary temperature and LF/HF ratio of children at 1 month were significantly lower after massage (p<0.05). Overall developmental age and expressive language domain of KIDS at 1 month were more developmental than in the non-massage group (p<0.05). Heart rate and HF were not significantly different after 1 month. Conclusion: It was found that when children received massage from their mothers for one-month, cardiac sympathetic nerve function was suppressed and the development of expressive language skills was promoted.